The Effectiveness of Using Picture Word Cards in Indonesian Language Learning at Elementary School: A Systematic Literature Review - Enjelyca, Bunga; Yasinta Mahendra; Rohmani (MIMBAR PGSD Undiksha, 2024)
The Indonesian language learning process at the level of basic education emits vital roles in building good and correct communication skills using the official language of the country. However, obstacles like low learning interest and poor outcomes often arise due to uncreative teaching approaches and less engaging media. Research was conducted a tidal analysis of the effectiveness of the use of picture cards as a tool in improving student language skills. Systematic Literature Review of Adding Method (SLR), this research is analyzing eight relevant articles published between 2019 and 2023. The article was obtained through the Google Scholer database to determine Indonesia. Furthermore, researchers choose data based on criteria with the theme of research in increasing the article on literature review. The results of the study show that the word card word card is positive impact on mastery of vocabulary, writing skills, and student creativity. The visual component effectively helps students overcome learning barriers like organizing ideas and understanding word context. It also fosters a more engaging and communicative learning environment, boosting motivation. It can be concluded that, a picture word card is an innovative solution that can support Indonesian learning more effectively, especially at the elementary school level. This research is a valuable contribution member in the development of relevant teaching methods and in accordance with student needs. The latest information is that this research is expected to win a guide for teachers in designing optimal and beneficial learning gift of students.